Systems-based approaches for evaluating residential-based hazards to inform environmental exposure intervention design - Oke, Oluwatobi Olamiposi, author; Carter, Ellison, advisor; Magzamen, Sheryl, committee member; Carlson, Kenneth, committee member; Sharvelle, Sybil, committee member (Colorado State University. Libraries, 2022)
Housing is an essential aspect of the physical built environment, where people spend most of their time, and a key determinant of health. Sub-standard and poor physical housing conditions (e.g., disrepair, deferred maintenance, and deteriorated physical environment) and exposures of inhabitants to lead, pests, air pollutants, and other indoor contaminants are associated with a wide range of health conditions, including respiratory infections, asthma, lead poisoning, injuries, chronic disease outcomes (e.g., cardiopulmonary conditions) and mental health illness. The environmental justice (EJ) research community that has focused on residential exposures has documented that adverse environmental exposures associated with residential settings and built environments are unevenly distributed and often disproportionately affect low-income and socioeconomically disadvantaged populations in the United States. Hence, work remains to be done if we intend to develop and maintain healthy residential environments for vulnerable population groups. However, a central challenge to this effort is the complex system of sources and source activities that contribute to and drive residential exposures, which makes it difficult to identify and isolate dominant sources. This dissertation sought to holistically investigate sources of three prevalent home-based exposures in the United States – i.e., flooding, lead, and indoor chemical mixtures. Through a combination of empirically-based and modeling approaches, this work brought together information on physical dwellings, their conditions and surroundings, the overlying sociodemographic characteristics of the people living in them, and the behaviors and activities that people undertake in their homes. The central hypothesis of this work has been that this approach would improve the identification of sources and their relative contributions to exposures in the residential environment. Significant findings from this work include: (i) socioeconomically disadvantaged populations in all three studies tended to have higher environmental exposures, regardless of exposure type, including natural hazards (i.e., floods), legacy pollution (i.e., lead), and pollutants driven by daily human activity (indoor air pollutants of outdoor origin); (ii) sources of environmental exposures varied within the same study and, at times, were more subtle than initially hypothesized in the literature, suggesting that the more holistic approaches taken in this work have practical value; and (iii) residential interventions to reduce adverse exposures could provide some measurable benefits to residents if customized to local occupants' needs in solving more building-related problems and providing higher residential satisfaction. In two of the three studies, we have worked closely or directly with the communities from which the data are collected. Thus, we expect outputs from this work to improve the design and delivery of home-based interventions for adverse environmental exposures through direct engagement with local decision-makers and more traditional scholarly communication channels.